Efforts in Improving Students 'Understanding Towards Students’ Choir Material Through Cooperative Learning Type Make A Match MIS (Manado Independent School) in Manado City - Meyny S. C Kaunang (AIBPM Publisher, 2020)
Research has been carried out with the application of the make a match type of cooperative learning model to increase student understanding in the Manado International School (MIS). The problem in this study is the low understanding of students in choir material at the beginning of school, and besides that it is also due to different cultures and countries. For this reason, this study aims to determine students' understanding of choir material by applying cooperative learning type make a match to MIS students in Manado. The research setting is all students both adolescent and adult level in the first batch 2018/2019. This research uses Classroom Action Research. The instruments used were observation of teacher or coach learning activities, observation of student activities, and practical tests. Analysis of the data used is interpretation based on the calculation of the frequency distribution with discussion based on the percentage scale and indicators of learning completeness determined by the curriculum. The results of this study can be said that learning on choir material through cooperative learning of make a match type MIS in the city of Manado was declared successful. The activities of students in the first cycle carried out 80% with quite good criteria and the second cycle carried out 100% with good criteria. From this data it is known that from the stages of learning and student activity gradually increased.